2012
DOI: 10.1371/journal.pone.0026551
|View full text |Cite|
|
Sign up to set email alerts
|

The Vividness of Happiness in Dynamic Facial Displays of Emotion

Abstract: Rapid identification of facial expressions can profoundly affect social interactions, yet most research to date has focused on static rather than dynamic expressions. In four experiments, we show that when a non-expressive face becomes expressive, happiness is detected more rapidly anger. When the change occurs peripheral to the focus of attention, however, dynamic anger is better detected when it appears in the left visual field (LVF), whereas dynamic happiness is better detected in the right visual field (RV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
35
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 27 publications
14
35
1
1
Order By: Relevance
“…the timing of the change, without sacrificing the realism of the expressive dynamics (e.g., Becker et al, 2012). The duration of the temporal unfolding of facial expressions of emotion (533 ms) was in line with other experiments generating dynamic facial expressions with methods similar to the present study (e.g., Arsalidou et al, 2011: 300 ms;Becker et al, 2012: 105 ms;Horstmann & Ansorge, 2009: 500 ms; Schultz & Pilz, 2009: 1040.…”
Section: Anger Superiority Effectsupporting
confidence: 90%
See 2 more Smart Citations
“…the timing of the change, without sacrificing the realism of the expressive dynamics (e.g., Becker et al, 2012). The duration of the temporal unfolding of facial expressions of emotion (533 ms) was in line with other experiments generating dynamic facial expressions with methods similar to the present study (e.g., Arsalidou et al, 2011: 300 ms;Becker et al, 2012: 105 ms;Horstmann & Ansorge, 2009: 500 ms; Schultz & Pilz, 2009: 1040.…”
Section: Anger Superiority Effectsupporting
confidence: 90%
“…Static facial stimuli do not reflect the information available from seeing a face in the real world and, thus, may elicit a form of processing that does not reflect the cognitive mechanisms naturally involved in emotion recognition (Foley, Rippon, Thai, Longe, & Senior, 2012). Becker, Neel, Srinivasan, Neufeld, and Kumar (2012) asked participants to identify the dynamic expression (happy or angry) of one or four faces. The stimuli were singleton faces or crowds of faces all showing the same emotional expression.…”
Section: Empirical Research On the Threat Advantage Effect Static Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, fear and anger obtained the lowest number of correct responses and the longest reaction times. Our findings thus coincide with those from previous studies that observed greater accuracy in detecting happiness than expressions of fear (Juth, Lundqvist, Karlsson, & Ohman, 2005;Kirouac & Dore, 1983), anger (Becker, Anderson, Mortensen, Neufeld, & Neel, 2011;Becker et al, 2012;Juth et al, 2005), and sadness (Srivastava & Srinivasan, 2010). These findings have led researchers to postulate that happy facial expressions are more visually-discriminable, probably because their communicative intent is less ambiguous than that of other expressions (Becker et al, 2011).…”
Section: Emotional Recognitionsupporting
confidence: 90%
“…In other studies happy faces were found most efficiently; a finding known as the happiness superiority effect (Juth, Lundqvist, Karlsson, & Öhman, 2005; D. V. Becker, Anderson, Mortensen, Neufeld, & Neel, 2011). This happiness superiority effect has also been shown in detection tasks that employed dynamic expressions of emotion instead of the still images used in visual search (D. V. Becker et al, 2012). Finally, some studies proffer that there is no evidence for the preferential detection of either expression and claim that previous reports reflect on low-level perceptual confounds rather than the emotion expressed (Purcell, Stewart & Skov, 1996;Purcell & Stewart, 2010).…”
mentioning
confidence: 70%